Financial Dominant of Activation of Investment Opportunities of Agro-food Production Entities of Ukraine. - Kukina, Natalia; Кукіна, Наталя Володимирівна; Makarenko, Yuliia; Melnyk, Larisa; Zavoloka, Yuliia; Sidnenko, Maryna (My University, 2024)
The article examines the financial toolkit for the distribution of resources of the public-private partnership institute, which changes the sources of the investment flow according to the balanced value of their target use in order to restore and ensure the activation of investment opportunities of agro-food production entities. It has been proven that the level of activation of sources of investment flow of agro-food production entities in a certain territory, provided that the public-private partnership institute is involved in this process, is normalized at a moderate risk and is attractive for investors. A comparison of the relative index of activation of the potential of investment opportunities of agro- food production subjects under the conditions of financial support of the public-private partnership institute in Ukraine and EU countries was made. The structure of the distribution of the sources of the investment flow of the public-private partnership institute. The nominal level of profitability of sources of investment flow from international partners in the distribution system of the institute of public-private partnership for the needs of realization of investment opportunities of producers of agro-food products has been calculated. The model of synergistic adaptation of the financial determinant in the own sources of the investment flow of agro-food production entities with the help of Euler circles is proposed. The estimated value of sources of investment flow for the renewal of agricultural machinery, mineral fertilizers of subjects of agro-food production of Ukraine with the support of the institute of public-private partnership was determined.
Фінансова домінанта активізації інвестиційних можливостей агропродовольчого виробництва суб'єкти України.
Keywords: Financial dominant; Investment opportunities; Investment capital; Investment flow; Financial support